Evaluation of the performance of diesel additive from the pyrolysis oil of waste foamed polystyrene and used motor oil - Reyes, Prince Elmer A. (2010)
Pyrolysis oil from waste foamed polystyrene and used motor oil of mass ratio 1:10 was produced in a batch pyrolyzer operating at 500°C for 2 hrs. The Cd, Cr, and Pb of the pyrolysis oil were analyzed at the research and Analytical Services Laboratory of the UP National Science Research Institute. Intended as a diesel additive, it was mixed with diesel fuel to form a 1% (v/v) and was characterized at the Chemical Engineering Laboratory and at the DOE-Energy Research and Testing Laboratory Services (ERTLS) while its performance compared to a neat diesel was evaluated at the UP Vehicle research and Testing Laboratory. Results show that the pyrolysis oil contains virtually no Cd, 0.071 ppm Cr, and 0.13 ppm Pb. Characterization of the diesel blend at the DOE-ERTLS indicates that the blend is a shade darker, denser, more viscous, more flammable, contains less sulfur and carbon residue at 10% bottons compared to the neat diesel. It has the same corrosivity as neat diesel, it also has no water and sediments, and its distillation temperature at 50% recovery is higher than that of neat diesel but the temperature for 90% recovery is lower. All fuel parameters, including the calculated cetane index, fall within the Philippine National Standards for on-road vehicles. Comparative testing of the blend at the UP VRTL shows that there might be no significant change in the mileage of the vehicle when the blend is used during drive cycle tests. The emission characteristics during the drive cycle test shows that an insignificant change in CO2, an increase in CO and NO, and a decrease in total hydrocarbon (THC) levels. Constant velocity testing, on the other hand shows increases in mileage at 60 and 80 kph but a decrease at 40 kph. No trend can be established to relate the change in mileage with velocity. Decrease of CO emissions is seen at all velocities during the constant velocity test, with the percent decrease decreasing with increasing velocity. On other hand, increase in NO is observed, with the percent increase increasing with increasing velocity. CO2 emissions decreased at 40 kph but increased at 60 kph, and increased further at 80 kph. On the other hand, THC emissions increased at 40 kph but decreased at 60 kph, and decreased further at 80 kph. Lastly, maximum power test show no significant change in the maximum power of the vehicle with the use of the blend.